HASIL STUDI KELAYAKAN BISNIS BAKSO HODO PRASMANAN - Khairina, Vika; Afifah, Kuni; Aprilia, Nurismil Khoir; Novantri, Ralda Cigra; Atiyah, Khoriratul; Fitriani, Intan (Fakultas Ekonomi dan Bisnis, 2023)
Bakso Hodo is the newest culinary delight in the city center of Situbondo serving various kinds of meatballs made from beef and also various additions such as fried foods, tofu and somay. Bakso Hodo has a branch in the East Besuki Alun-alun area. Bakso Hodo has a very special concept and is currently popular in Situbondo, served at a buffet. This research method is observation, interviews and documentation with the admin who is the brother of the owner of the Bakso Hodo.